Integrated analysis of microRNA and mRNA expression profiles highlights the complex and dynamic behavior of toosendanin-induced liver injury in mice - Lu, Xiaoyan (Sci Rep, 2016)
Triterpenoid Toosendanin (TSN) exhibits a plenty of pharmacological effects in human and great values in agriculture. However, the hepatotoxicity caused by TSN or Melia-family plants containing TSN used in traditional Chinese medicine has been reported, and the mechanisms of TSN-induced liver injury (TILI) still remain largely unknown. In this study, the dose- and time-dependent effects of TSN on mice liver were investigated by an integrated microRNA-mRNA approach as well as the general toxicological assessments. As the results, the dose- and time-dependent liver injury and alterations in global microRNA and mRNA expressions were detected. Particularly, 9-days 80 mg/kg TSN exposure caused most serious liver injury in mice, and the hepatic adaptation to TILI was unexpectedly observed after 21-days 80 mg/kg TSN administration. Based on the pathway analysis of the intersections between predicted targets of differentially expressed microRNAs and differentially expressed mRNAs at three time points, it revealed that TILI may be caused by glutathione depletion, mitochondrial dysfunction and lipid dysmetabolism, ultimately leading to hepatocytes necrosis in liver, while liver regeneration may play an important role in the hepatic adaptation to TILI. Our results demonstrated that the integrated microRNA−mRNA approach could provide new insight into the complex and dynamic behavior of TILI.